INTESTINAL MICROBIOCENOSIS AND PROBIOTICS IN FORMATION OF IMMUNE RESPONSE AND HEALTH OF CHILDREN - E.M. Bulatova; N.M. Bogdanova ("Paediatrician" Publishers LLC, 2010)
The article reviews the modern data on structure and functions of intestinal micro flora. Possible ways of activation of acquired immune response and food tolerance forming are shown. Positive role of probiotics in treatment and prophylaxis of acute respiratory infections is described. Key words: intestinal micro flora, expression of genes, immunity, secretory immunoglobulin A (sIgA), toll-like receptors (TSRs), cross-talk. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):37-44)